PDGF-BB accelerates TSCC via fibroblast lactates limiting miR-26a-5p and boosting mitophagy - Jianguo Xu; Li Bian; Dingyun You; Ziliang Li; Tingting Wang; Yiting Li; Xiaobin Ren; Yongwen He (Cancer Cell International, 2024)
Abstract The tumor microenvironment and cancer-associated fibroblasts (CAFs) play crucial roles in tumor development, and their metabolic coupling remains unclear. Clinical data showed a positive correlation between PDGF-BB, CAFs, and glycolysis in the tumor microenvironment of oral tongue squamous cell carcinoma patients. In vitro, CAFs are derived from hOMF cells treated with PDGF-BB, which induces their formation and promotes aerobic glycolysis. Mitophagy increased the PDGF-BB-induced formation of CAF phenotypes and aerobic glycolysis, while autophagy inhibition blocked PDGF-BB-induced effects. Downregulation of miR-26a-5p was observed in CAFs; upregulation of miR-26a-5p inhibited the expression of mitophagy-related proteins ULKI, Parkin, PINK1, and LC3 and aerobic glycolysis in PDGF-BB-induced CAFs. PDGF-BB-induced CAFs promoted tumor cell proliferation, invasion, metastasis, NF-κB signaling pathway activation, and PDGF-BB secretion. Thus, PDGF-BB is associated with lactate-induced CAF formation and glucose metabolism reprogramming. These findings indicate potential therapeutic targets in oral tongue squamous cell carcinoma.